Rare embryonal tumor of the central nervous system in newborns: case report and comparative clinical analysis - Panina, A. S.; Kuzyk, P. V.; Savchuk, T. V.; Zhovnir, V. A.; Sadykova, A. Zh. (Modern medical technology, 2025)
Aim: to conduct a clinical and morphological analysis of a case of central nervous system (CNS) embryonic tumor not otherwise specified (NOS) and to determine its key pathogenetic features. Materials and methods. A retrospective analysis was conducted of an autopsy case involving a deceased premature female neonate diagnosed with a CNS embryonal tumor, NOS. The material was obtained from the Division of Pathological Anatomy of the National Specialized Children’s Hospital “Ohmatdyt” of the Ministry of Health of Ukraine. The morphological diagnosis was established based on macroscopic and microscopic examination. Results. The findings indicate an intrauterine origin of the CNS embryonal tumor NOS and the presence of characteristic morphological features that correlate with aggressive tumor behavior, including multiple necroses, hemorrhages, and pseudorosettes formations composed of poorly differentiated cells. The study emphasizes the importance of fetal magnetic resonance imaging in complex cases of prenatal hydrocephalus as a diagnostic tool and for determining further pregnancy management strategies. Conclusions. The presented case highlights the need for an interdisciplinary approach to the diagnosis and care of newborns with CNS embryonal tumors and the creation of prognostic models for delivery outcomes in the presence of this pathology.